Consumers' Behaviors and Attitudes toward Doggy Bags: Identifying Barriers and Benefits to Promoting Behavior Change. Issue 5 (4th July 2018) - Mirosa, Miranda; Liu, Yang; Mirosa, Romain
ABSTRACT: This study identifies barriers and benefits of consumers' current doggy bag behaviors and provides the information required to run an effective community-based social marketing campaign encouraging consumers to take their uneaten restaurant and café food home. This is done by applying a two-stage methodology, including quantitatively analyzing existing survey data and qualitatively investigating focus group discussion. Multiple barriers to widespread doggy bag participation were common and varied for different individuals and included both convenience and social stigma-related factors. The rational appeal of "saving money" was found to be the most effective motivator for encouraging doggy bag usage, especially for women, young people, students/unemployed, and low-income earners. Social marketing strategies and behavior change tools can be developed to remove the barriers and enhance the benefits of using doggy bags, such as developing positive social norms around using doggy bags and highlighting the financial incentive of using them. This research contributes to a limited but growing literature on out-of-home food waste and provides practicable insights for both public policy and for the food service sector for future initiatives aiming to reduce food waste.